Decision To Refinance a High-Rate Mortgage. (U.S. Congressional Research., 1983)
Discusses and illustrates the factors involved in deciding whether to refinance a high-rate mortgage. Covers types of mortgages, interest rates, fees, and income tax deductions. Includes tables.